(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Herbal medicines have been used traditionally to manage various diseases, including diabetes. Herbs such as Camellia sinensis, Cinnamomum verum, Syzygium aromaticum, Curcuma longa, and Elettaria cardamomum have been observed to have pharmacological properties. The main objective was to see if this polyherbs composite can be an adjuvant therapy for the diabetic patient. We created a formulation that included multiple herbal components by combining individual ethanolic extracts of traditional medicinal herbs in a predefined ratio. HPTLC was carried out to identify the bioactive constituents present in the formulation. Type 2 diabetes mellitus (T2DM) was experimentally induced in male Wistar rats by administering STZ, 50 mg/kg, i.p., followed by nicotinamide 120 mg/kg, p.o. After confirmation of hyperglycemia, rats were treated orally with the polyherbal formulation (250 and 500 mg/kg) and Glibenclamide (0.25 mg/kg) for 21 days. At the end of the treatment, body weight, serum insulin, and pancreatic tissue were obtained for analysis of antioxidants, inflammatory markers, and histopathological examination. HPTLC indicates the presence of stable and the most dominant bioactive constituents in the polyherbal extract. The post-treatment body weight was statistically not changed within the groups, except in the STZ control (p<0.05) group. There was a significant change in blood glucose and serum insulin level in the STZ control group (p<0.01) and a reduction in the level of glucose and a rise in insulin levels after administration of the test formulation and Glibenclamide (p<0.05, p<0.01). The concentration linked to the antioxidant enzyme GPx showed a marked elevation in the test formulation (p<0.05) and lower LPO levels. Increased levels of TNF-α and IL-6 were reported in the STZ control group (p<0.001) but were significantly lower after administration of the formulation (p<0.05, p<0.01). Pancreatic tissue showed well-organized, significant restoration of pancreatic structure, and islet integrity was observed. The polyherbal formulation showed a significant reduction in hyperglycemia and antioxidant and anti-inflammatory effects, supporting its potential as a complementary therapy for diabetes management.